Nutritional value of palm kernel meal, fruit of the royal palm tree (Roystonea regia), for feeding broilers - Martínez, Madeleidy; Vives, Yesenia; Rodríguez, Bárbara; Pérez, O. G.; Herrera, Magalys (Cuban Journal of Agricultural Science, 2021)
To determine the nutritional value of Roystonea regia fruit (palm kernel) meal for feeding broilers, an experiment was developed with 40 male animals, distributed in four treatments according to a completely randomized design: control (corn-soybean paste) and inclusion of 5, 10 and 15 % of palm kernel meal. The physical and chemical composition of the ingredient was calculated using descriptive statistics and Pearson correlation was applied to demonstrate the association degree among indicators. Apparent fecal retention of nutrients was studied by total excreta collection method. Crude protein was moderate, while ether extract and fiber fractionation contents were high. The analysis of physical properties showed low solubility and greater buffering capacity against acids with respect to bases (0.61 vs 0.24 meq). There was a high correlation between chemical and physical characteristics (greater than 85 %). Apparent fecal retention of neutral detergent fiber showed a reduction from 10 % inclusion of palm kernel meal in the ration, while control and 5 % did not differ among treatments. Regarding ether extract, the highest coefficient was reached with 5 %, and the lowest with 15 % (88.04 and 83.38 %, respectively) (P<0.05). It is concluded that palm kernel meal has adequate nutritional value for feeding broilers. Key words: poultry, palm fruit meal, physical and chemical composition, apparent fecal nutrient retention